Reports of Judgments, Advisory Opinions and Orders 2023 Bound Volume I - International Court of Justice (United Nations, 2025)
This new edition of the ICJ’s signature series includes all the decisions taken by the International Court of Justice in 2023. The I.C.J. Reports 2023 comes in two hard-bound volumes and includes a comprehensive index.